Evaluation of Antioxidant and Antibacterial Properties of Rhododendron arboreum, Acmella calva and Trifolium repens of Nepal (Tribhuvan University Journal of Microbiology, 2024)
Objectives: To evaluate the antioxidant and antibacterial properties of Rhododendron arboreum, Acmella calva and Trifolium repens.Methods: Different extracts of the R. arboreum, A. calva and T. repens were used for detection of total phenolic content and total flavonoid content. 2, 2-diphenyl-1-picryl hydrazyl (DPPH) assay was performed to evaluate the antioxidant activity. Antimicrobial activity was carried out by agar well diffusion method. Minimum Bactericidal Concentration (MBC) was determined by broth micro dilution assay.Results: Ethyl acetate extract of R. arboreum had high total phenolic content (128.36±1.65) and total flavonoid content (107.3±0.92). The high antioxidant activity with IC50 value of 34.97µg/mL was shown by ethyl acetate extract of R. arboreum. The ethyl acetate extract of R. arboreum showed maximum zone of inhibition against E. coli, K. pneumoniae, P. aeruginosa, A. baumanii, S. aureus and E. fecalis with the lowest MBC values.Conclusion: R. arboreum, A. calva and T. repens have antimicrobial activity and compounds with antioxidant activity and should be investigated further for potential medicinal use.